Strategy to minimize fraud in village fund financial governance - Sahala Purba; Wie Shi Wudjud; Santy Aji Sitohang (Institute of Accounting Research and Novation (IARN), 2025)
The purpose of this research is to find out and analyze whether it can minimize fraud in villagers fund governance when viewed from the capabilities of villagers officials, agency intentions, openness and internal control standards. The research method uses a questionnaire, with a population of all villagers government officials in Sunggal District, Deli Serdang Regency, North SumatraThis sampling used criteria including the villagers head as the holder of villagers governance authority, the villagers secretary as the technical coordinator of activities, the villagers treasurer as the person responsible for villagers financial administration and the BPD as the representative of villagers residents. The implementation time is September - November 2024. The results of this research are that the capabilities of villagers officials, agency intentions, openness and internal control standards can have a positive and significant impact on minimizing fraud in villagers fund governance in Sunggal District, Deli Serdang Regency, either partially or simultaneously.